A novel technique for digital image watermarking in frequency domain - Singh A.K.; Dave M.; Mohan A. (My University, 2025)
New opportunities have been explored in social, business, entertainment and scientific fields due to the development of high speed computer networks and that of, internet in particular. Ironically, the cause for the development is apprehensive because of the use of digital formatted data. Digital media has several advantages over analog media such as high fidelity copying easy editing and high quality. Software products which hide information within digital audio, images and video files have been introduced to address these growing concerns. One of the techniques of data hiding is digital watermarking. The watermarking is the process of embedding a signal in to other signal robustly and invisibly at the same time, the embedded signal is called watermark and the other signal is called cover or host signal. In this paper we are presents a brief overview of digital image watermarking techniques in spatial and frequency domain, advantages of frequency domain over spatial domain techniques and proposed a watermarking algorithm in frequency domain by using the discrete wavelet transform. © 2012 IEEE.